THE IMPLEMENTATION OF CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOL - Hidayat, Nur; Bujuri, Dian Andesta (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract: The aim of this research was to find out the implementation of character education in Islamic boarding school (Ponpes) of Ibnul Qoyyim in Yogyakarta and Al-Hidayah in Jambi. The method used of this research was qualitative method with case study approach. The data were obtained through interview, observation, and documentation. The research subjects were selected using purposive sampling. Data analysis technique used referred to Miles and Huberman model, namely reducing data, displaying data, and concluding. The findings indicated that there were similar methods applied to teach character education in both Ponpes. Both of them integrated vision, mission, and all activities program into character education values through co-curricular, intracurricular, extracurricular, and habituation. Islamic students (Santri) practiced the values such as religious, politeness, discipline, honest, hard work, independent, responsible, mutual help, tolerant, caring the social environment in daily activities. The minimum control was able to give opportunity for Santri to avoid negative behavior. The character education which was programmed and integrated to all activities in those Ponpes was quite effective to build Islamic students’ character which needed intensive collaboration between parents and society to educate and to control Santri when they were outside Ponpes area. Abstrak: Tujuan penelitian ini adalah untuk mempelajari pelaksanaan pendidikan karakter di pesantren Ibnul Qoyyim di Yogyakarta dan Al-Hidayah di Jambi. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan menggunakan studi kasus. Data diperoleh melalui wawancara, observasi, dan dokumentasi. Subjek penelitian dipilih menggunakan purposive sampling. Teknik analisis data yang digunakan mengacu pada model Miles dan Huberman, yaitu mereduksi data, menampilkan data, dan menyimpulkan. Hasil penelitian menunjukkan adanya kesamaan metode yang digunakan kedua Ponpes tersebut. Keduanya mengintegrasikan visi, misi, dan program kegiatan ke dalam nilai-nilai pendidikan karakter melalui ko-kurikuler, intrakurikuler, ekstrakurikuler, dan habituasi. Santri mempraktikkan nilai-nilai seperti agama, kesopanan, disiplin, jujur, kerja keras, mandiri, bertanggung jawab, saling membantu, toleran, peduli terhadap lingkungan sosial dalam kehidupan sehari-hari. Kontrol minimum mampu memberi kesempatan bagi Santri untuk menghindari perilaku negatif. Pendidikan karakter yang diprogramkan dan terintegrasi ke semua kegiatan di Ponpes cukup efektif untuk membangun karakter Santri yang membutuhkan kolaborasi intensif antara orang tua dan masyarakat untuk mendidik dan mengontrol Santri ketika mereka berada di luar wilayah Ponpes.